Studies on gonococcus infection. VIII. 125Iodine labeling of gonococci and studies on their in vitro interactions with eukaryotic cells. - Swanson, J (1975)
Intact gonococci (GC) have been labeled with 125iodine by the lactoperoxidase plus hydrogen peroxide procedure. The specific activities of types 2, 4, and 4 GC have been determined and are found to show small differences as follows: T4 greater than T2 greater than T4. 125I-labeled GC have been studied for their associations with both leukocytes and tissue culture cells. 125I-labeled GCshow the following relative order of association with the leukocytes: T2 equals T4* greater than T4. This contrasts with the relative degree of interaction between the GC and tissue culture cells, which follows the relative order: T2 greater than T4 equals T4*. Trypsin pretreatment of GC markedly reduces the association of all three types (T2, T4 AND T4*) with leukocytes but does not alter the level of attachment of any of the gonococcal types with tissue culture cells.